Tradisi Pernikahan Nyandung Watang di Desa Bambe Kecamatan Driyorejo Kabupaten Gresik - Dian Purwanti; I Wayan Arsana (Journal on Education, 2024)
Tradition refers to longstanding customs inherited within a society that are still actively practiced. It typically encompasses old values, norms, and customs upheld by specific groups within a region. A descriptive qualitative research approach was employed to gather data on the Nyandung Watang marriage tradition in Bambe Village, Driyorejo District, Gresik Regency. Data collection methods included observation, interviews, and documentation. Findings revealed a shift in the Nyandung Watang tradition, particularly when it coincides with the passing of a grandfather, grandmother, or other family members of the bride or groom. This alteration in tradition reflects the influence of contemporary developments and changing societal knowledge. Presently, the Nyandung Watang wedding tradition involves presenting staple foods, processed items, kitchen utensils, and spices to the bereaved family as a gesture of respect.